Zinc and selenium status in critically ill patients according to severity stratification - Cirino Ruocco, Marina Augusta [UNESP]; Pacheco Cechinatti, Evelin Drociunas; Barbosa, Fernando; Navarro, Anderson Marliere [UNESP] (Elsevier, 2018)
Objective The aim of this study was to evaluate the concentrations of zinc and selenium in different biological materials and to associate them with the clinical severity score according to the Simplified Acute Physiology Score (SAPS) III. Methods The study was conducted in a 10-bed general intensive care unit of the Américo Brasiliense State Hospital/SP, with 95 patients stratified by the SAPS III score cutoff points (63.5 points) as less or more severe and by the diagnosis of sepsis. Analyses of zinc and selenium concentrations in plasma, erythrocytes, and urine were conducted. Results Plasma concentrations were found to be lower than the reference values for both micronutrients (8.4 ± 4 and 0.18 ± 0.06 μmol/L, respectively, for zinc and selenium), and urinary zinc concentration was higher than the reference (38.6 ± 35.8 μmol/24 h). The mean selenium plasma concentration was significantly lower in patients with greater severity, which was not observed for zinc (P > 0.05). The mean selenium plasma and erythrocyte concentrations were significantly different between the groups diagnosed with sepsis, which was not observed in the analysis of zinc. Albumin levels (r = −0.26; P = 0.01) and C-reactive protein (r = 0.40; P < 0.001) correlated with the SAPS III severity score. Conclusion Plasma concentrations of zinc and selenium are low in critically ill patients upon admission to the intensive care unit and may make these patients more susceptible to oxidative stress. The low concentration of erythrocyte selenium may represent an inadequate intake by this population. Additional studies using new biomarkers should be performed with the objective of identifying values for the local population.
Keywords: Critically ill; SAPS III; Selenium; Zinc